Prisons, sida et divulgation de renseignements médicaux. Analyse juridique et éthique - Jürgens, Ralf; Gilmore, Norbert (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
The article addresses some of the issues raised in federal correctional institutions by the generation and communication of personal medical information pertaining the HIV infection. It examines, first, whether medical information pertaining to federal inmates — information considered confidential between medical staff and an inmate — can be disclosed absent the inmate's consent. It then examines what conditions or criteria determine whether or not such disclosure is ethically and legally justifiable, and if disclosure is justified, what conditions apply to its disclosure. Finally, specific situations in which a claim for disclosure may arise are examined.The article concludes that in federal correctional institutions, the disclosure of personal medical information absent consent of the person is seldom justifiable. In most situations, such disclosure is unnecessary and even appears to be counterproductive or harmful. Measures that can be undertaken to prevent exposure to and infection with HIV have to be undertaken regardless of whether an inmate or staff member is or is not known, to staff, wardens, or inmates, to be infected with HIV.